Detection of Symmetries in Cattle Skulls - Casanova, P.M. Parés-; Gambo, B.G.; Yahaya, A.; Olopade, J.O. (Journal of Buffalo Science, 2018)
A sample of adult individuals from two ethnological groups (“European” n=36 and “African” n=10) that exhibited a normal craniofacial phenotype on their dorsal aspect was studied by means of geometric morphometric methods. Eleven landmarks were selected, corresponding to the neurocranium and viscerocranium. Both fluctuating as directional asymmetries were detected. The latter accounted for the largest proportion of the total variation, causing the main variation in symmetric shape, the former being higher in Kuri cattle. Detected fluctuating asymmetries could indicate an overall poor quality or general low health condition of individuals, due to the harder conditions (climatic, tropical) in which Kuri breed must thrive. Detected directional asymmetry, on the other side, could reflect just a mere functional lateralization of Bos taurus, as it has been established for other domestic animals.